Use of deterministic models in sports and exercise biomechanics research - Chow, J. W.; Knudson, D. V. (Sports Biomechanics, 2011)
A deterministic model is a modeling paradigm that determines the relationships between a movement outcome measure and the biomechanical factors that produce such a measure. This review provides an overview of the use of deterministic models in biomechanics research, a historical summary of this research, and an analysis of the advantages and disadvantages of using deterministic models. The deterministic model approach has been utilized in technique analysis over the last three decades, especially in swimming, athletics field events, and gymnastics. In addition to their applications in sports and exercise biomechanics, deterministic models have been applied successfully in research on selected motor skills. The advantage of the deterministic model approach is that it helps to avoid selecting performance or injury variables arbitrarily and to provide the necessary theoretical basis for examining the relative importance of various factors that influence the outcome of a movement task. Several disadvantages of deterministic models, such as the use of subjective measures for the performance outcome, were discussed. It is recommended that exercise and sports biomechanics scholars should consider using deterministic models to help identify meaningful dependent variables in their studies.